2021
DOI: 10.1155/2021/9975586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of MKAVCFSL Derived from Bighead Carp (Hypophthalmichthys nobilis) Flesh on Antioxidant Activity in Caco-2 Cells In Vitro

Abstract: The effect of an antioxidative peptide Met-Lys-Ala-Val-Cys-Phe-Ser-Leu (MKAVCFSL) on oxidative stress in Caco-2 cell lines was investigated. Caco-2 cells exposed to excess oxidative stress could be restored when pretreated with the peptide. Reactive oxygen species (ROS) and malondialdehyde (MDA) within the cells could be scavenged by MKAVCFSL. The peptide could also enhance the activity of glutathione peroxidase (GPx), glutathione reductase (GR), and superoxide dismutase (SOD), while catalase (CAT) activity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Hydrophobic amino acids Ala and Gly can provide H + and enhance synergy with other amino acids to display antioxidant properties (Li et al, 2021 ). Previously studies have showed that some similar peptides, such as MKAVCFSL (Zhang et al, 2021 ), IYVFVR (Zhang et al, 2019 ), and WVSPLAGRT (Bollati et al, 2022 ), contained more aromatic and hydrophobic amino acids and efficiently ameliorated the damage of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic amino acids Ala and Gly can provide H + and enhance synergy with other amino acids to display antioxidant properties (Li et al, 2021 ). Previously studies have showed that some similar peptides, such as MKAVCFSL (Zhang et al, 2021 ), IYVFVR (Zhang et al, 2019 ), and WVSPLAGRT (Bollati et al, 2022 ), contained more aromatic and hydrophobic amino acids and efficiently ameliorated the damage of oxidative stress.…”
Section: Resultsmentioning
confidence: 99%